2009
DOI: 10.1523/jneurosci.4997-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

The Involvement of Hypothalamic Sleep Pathways in General Anesthesia: Testing the Hypothesis Using the GABAAReceptor β3N265M Knock-In Mouse

Abstract: The GABA A receptor has been identified as the single most important target for the intravenous anesthetic propofol. How effects at this receptor are then translated into a loss of consciousness, however, remains a mystery. One possibility is that anesthetics act on natural sleep pathways. Here, we test this hypothesis by exploring the anesthetic sensitivities of GABAergic synaptic currents in three specific brain nuclei that are known to be involved in sleep. Using whole-cell electrophysiology, we have record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
1
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 60 publications
4
97
1
2
Order By: Relevance
“…74 Inhibiting orexinergic activity was found to prolong emergence from isoflurane anesthesia, 75 but orexins may not be important for the actions of halothane 76 or dexmedetomidine. 77 As we have previously argued, 78 interpretation of such findings is fraught with difficulties due to the behaviourally activating/ sedating effects of neurotransmitter agonists/antagonists, respectively. Clearly, there is a difference as to whether a particular neurotransmitter system can affect anesthesia (by altering the arousal baseline) and whether it is actually relevant to the mechanism of action of these drugs.…”
Section: Sleep and General Anesthesia 143mentioning
confidence: 99%
See 3 more Smart Citations
“…74 Inhibiting orexinergic activity was found to prolong emergence from isoflurane anesthesia, 75 but orexins may not be important for the actions of halothane 76 or dexmedetomidine. 77 As we have previously argued, 78 interpretation of such findings is fraught with difficulties due to the behaviourally activating/ sedating effects of neurotransmitter agonists/antagonists, respectively. Clearly, there is a difference as to whether a particular neurotransmitter system can affect anesthesia (by altering the arousal baseline) and whether it is actually relevant to the mechanism of action of these drugs.…”
Section: Sleep and General Anesthesia 143mentioning
confidence: 99%
“…For instance, orexinergic tone appears to be differentially inhibited by propofol and dexmedetomidine, but exogenous orexin can attenuate LORR caused by both. 77 Furthermore, the fact that both drugs appear to enhance VLPO activity and decrease TMN activity 22,74 indicates that studies examining the effects of drugs affecting the histamine system may be behaviourally relevant. Also, in vitro studies looking at neuronal responses to anesthetics can be useful, e.g., the b 3 N265M knockin mouse is behaviourally less sensitive to propofol and etomidate.…”
Section: Sleep and General Anesthesia 143mentioning
confidence: 99%
See 2 more Smart Citations
“…Histaminergic neurons are considered a key in endogenous arousal of the neuronal circuitry; thus, anesthetics produce their hypnotic effects through the neuronal circuitry. One study reported that the lower sensitivity to propofol in genetically mutated mice was mirrored by a reactivity to GABAergic inhibitory postsynaptic currents (IPSCs) in the tuberomammillary nucleus of the hypothalamus [52]. These results indicate that central histaminergic neurons play a crucial role in emergence from general anesthesia via the endogenous arousal neuronal circuitry.…”
Section: Histaminementioning
confidence: 99%